2007
DOI: 10.1103/physrevlett.99.046803
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Controlled Transport Properties of Metallic Atoms along Carbon Nanotube Surfaces

Abstract: The diffusion mechanism of indium atoms along multiwalled carbon nanotubes is studied by means of photoemission spectromicroscopy and density functional theory calculations. The unusually high activation temperature for diffusion (approximately 700 K), the complex C 1s and In 3d5/2 spectra, and the calculated adsorption energies and diffusion barriers suggest that the indium transport is controlled by the concentration of defects in the C network and proceeds via hopping of indium adatoms between C vacancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…The C 1s components, related to vacancy defects in the C cage, and the O 1s components, corresponding to the different possible O-bonding configurations, were identified by comparing with the spectra from ''perfect'' and defective HOPG samples subjected to the same oxygen treatments. [28] The assignments of the C 1s and O 1s components were based on the theoretical prediction for the core-level shifts and the reported spectra of compounds containing the particular oxygen functional groups. [13,[28][29][30][31][32][33][34][35] Small deviations in the core-level binding energies due to variations in the density and actual bonding configuration of oxygen on the surface has to be considered as well.…”
Section: à2mentioning
confidence: 99%
See 2 more Smart Citations
“…The C 1s components, related to vacancy defects in the C cage, and the O 1s components, corresponding to the different possible O-bonding configurations, were identified by comparing with the spectra from ''perfect'' and defective HOPG samples subjected to the same oxygen treatments. [28] The assignments of the C 1s and O 1s components were based on the theoretical prediction for the core-level shifts and the reported spectra of compounds containing the particular oxygen functional groups. [13,[28][29][30][31][32][33][34][35] Small deviations in the core-level binding energies due to variations in the density and actual bonding configuration of oxygen on the surface has to be considered as well.…”
Section: à2mentioning
confidence: 99%
“…[19] These results have demonstrated that the graphene cage of aligned multiwalled CNTs, which can be grown only by chemical vapor deposition (CVD), [22][23][24][25] usually contains up to 0.03-0.06 of monolayer (ML) single and multiple vacancy defects. [19] In the present work, we exploit the formation of oxygen functional groups and the morphological changes of aligned multiwalled CNTs upon exposure to atomic oxygen at different temperatures. Gas-phase oxidation has an advantage over chemical oxidation with acids, peroxides, or permanganate, because it does not generate liquid waste.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In this respect, X-ray photoelectron spectroscopy (XPS) has provided important contributions to semiconductor research, monitoring changes in the chemical state, band bending, and photoemission-induced surface charging [12,18,19,21]. Synchrotron light XPS has become a true microscopy technique, used recently for characterization of nanotubes, nanobelts, and NWs [22][23][24]. This study of undoped GaAs NWs prior to, and after, exposure to oxygen ambient demonstrates that by means of scanning photoelectron microscopy (SPEM) [25] it is possible to examine the interplay between NW diameter and conductance, combining full control of the surface chemical state with contactless monitoring of the changes in the conductivity along the axis of the NWs.…”
Section: Introductionmentioning
confidence: 99%
“…We have already studied the oxidation of CNTs [9] and carried out many experiments to investigate the mass transport of metals deposited on the CNTs [10]. At the present, we are able to take SPEM image of CNTs down to 50 nm in diameter.…”
Section: B Multi-wall Cntsmentioning
confidence: 99%